Liver Function Test Abnormalities in Experimental and Clinical Plasmodium vivax Infection - Odedra, Anand; Webb, Lachlan; Marquart, Louise; Britton, Laurence J.; Chalon, Stephan; Moehrle, Joerg J.; Anstey, Nicholas M.; William, Timothy; Grigg, Matthew J.; Lalloo, David G.; Barber, Bridget E.; McCarthy, James S. (The American journal of tropical medicine and hygiene, 2020)
Liver transaminase elevations after treatment in malaria volunteer infection studies (VISs) have raised safety concerns. We investigated transaminase elevations from two human VISs where subjects were treated with chloroquine ( = 24) or artefenomel ( = 8) and compared them with studies in Thailand ( = 41) and Malaysia ( = 76). In the VISs, alanine transaminase (ALT) increased to ≥ 2.5 × upper limit of normal (ULN) in 11/32 (34%) volunteers, peaking 5-8 days post-treatment. Transaminase elevations were asymptomatic, were not associated with elevated bilirubin, and resolved by day 42. The risk of an ALT ≥ 2.5 × ULN increased more than 4-fold (odds ratio [OR] 4.28; 95% CI: 1.26-14.59; = 0.02) for every log increase in the parasite clearance burden (PCB), defined as the log-fold reduction in parasitemia 24 hours post-treatment. Although an elevated ALT ≥ 2.5 × ULN was more common after artefenomel than after chloroquine (5/8 [63%] versus 6/24 [25%]; OR 5.0; 95% CI: 0.91-27.47; = 0.06), this risk disappeared when corrected for PCB. Peak ALT also correlated with peak C-reactive protein ( = 0.44; = 0.012). Elevations in ALT (≥ 2.5 × ULN) were less common in malaria-endemic settings, occurring in 1/41 (2.5%) Thai patients treated with artefenomel, and in none of 76 Malaysians treated with chloroquine or artemisinin combination therapy. Post-treatment transaminase elevations are common in experimental infection but do not appear to impact on participant safety. Although the mechanism of these changes remains uncertain, host inflammatory response to parasite clearance may be contributory.